2017
DOI: 10.3791/55642
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Muscle-cell Based Actuator and Self-stabilizing Biorobot - PART 1

Abstract: Biological machines often referred to as biorobots, are living cell- or tissue-based devices that are powered solely by the contractile activity of living components. Due to their inherent advantages, biorobots are gaining interest as alternatives to traditional fully artificial robots. Various studies have focused on harnessing the power of biological actuators, but only recently studies have quantitatively characterized the performance of biorobots and studied their geometry to enhance functionality and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…More complex swimming devices have also been developed, including a PDMS-based self-stabilizing swimming robot powered by cardiomyocytes (2830). The device consisted of three layers: a PDMS-Nickel composite layer, a PDMS cantilever layer, and a PDMS-microballoon composite layer.…”
Section: Organic Components In Roboticsmentioning
confidence: 99%
“…More complex swimming devices have also been developed, including a PDMS-based self-stabilizing swimming robot powered by cardiomyocytes (2830). The device consisted of three layers: a PDMS-Nickel composite layer, a PDMS cantilever layer, and a PDMS-microballoon composite layer.…”
Section: Organic Components In Roboticsmentioning
confidence: 99%
“…Holley et al [4] developed a self-stabilized swimming bionic robot, which can complete pitching, depth and rolling without external intervention. Kashi et al [5] observed the liquid flow around the flippers simulated by the sea lion robot using particle imaging velodrometer.…”
Section: Introductionmentioning
confidence: 99%